Publisher’s Note: “Review Article—Dielectrophoresis: Status of the theory, technology, and applications” [Biomicrofluidics 4, 022811 (2010)] - Pethig, Ronald (American Institute of Physics, 2010)
A review is presented of the present status of the theory, the developed technology and the current applications of dielectrophoresis (DEP). Over the past 10 years around 2000 publications have addressed these three aspects, and current trends suggest that the theory and technology have matured sufficiently for most effort to now be directed towards applying DEP to unmet needs in such areas as biosensors, cell therapeutics, drug discovery, medical diagnostics, microfluidics, nanoassembly, and particle filtration. The dipole approximation to describe the DEP force acting on a particle subjected to a nonuniform electric field has evolved to include multipole contributions, the perturbing effects arising from interactions with other cells and boundary surfaces, and the influence of electrical double-layer polarizations that must be considered for nanoparticles. Theoretical modelling of the electric field gradients generated by different electrode designs has also reached an advanced state. Advances in the technology include the development of sophisticated electrode designs, along with the introduction of new materials (e.g., silicone polymers, dry film resist) and methods for fabricating the electrodes and microfluidics of DEP devices (photo and electron beam lithography, laser ablation, thin film techniques, CMOS technology). Around three-quarters of the 300 or so scientific publications now being published each year on DEP are directed towards practical applications, and this is matched with an increasing number of patent applications. A summary of the US patents granted since January 2005 is given, along with an outline of the small number of perceived industrial applications (e.g., mineral separation, micropolishing, manipulation and dispensing of fluid droplets, manipulation and assembly of micro components). The technology has also advanced sufficiently for DEP to be used as a tool to manipulate nanoparticles (e.g., carbon nanotubes, nano wires, gold and metal oxide nanoparticles) for the fabrication of devices and sensors. Most efforts are now being directed towards biomedical applications, such as the spatial manipulation and selective separation/enrichment of target cells or bacteria, high-throughput molecular screening, biosensors, immunoassays, and the artificial engineering of three-dimensional cell constructs. DEP is able to manipulate and sort cells without the need for biochemical labels or other bioengineered tags, and without contact to any surfaces. This opens up potentially important applications of DEP as a tool to address an unmet need in stem cell research and therapy.